Dicer Nuclease‐Promoted Production of Let7a‐1 MicroRNA Is Enhanced in the Presence of Tryptophan‐Containing Amphiphilic Peptides. Issue 11 (2nd July 2014) - Hyun, Soonsil; Han, Areum; Jo, Myung Hyun; Hohng, Sungchul; Yu, Jaehoon
Abstract A library of Trp‐containing amphiphilic peptides was synthesized and screened for the ability to bind to pre‐miRNA targets. Two members of this family, peptides Ac‐WKKLLKWLKKLLKLAG‐NH2 (2 b) and Ac‐WKKLLKWLKKLLDabLAG‐NH2 (4 b) were found to have nanomolar binding affinities to pre‐let7a‐1. Peptides 2 b and 4 b caused an increase in the in vitro Dicer cleavage of pre‐let7a‐1. This observation was confirmed by a cell‐based assay, the results of which show an up to 50 % increase in Dicer activity. Enhanced expression of let7a‐1 promoted by the peptides results in specific reductions of target mRNAs. The results of a microarray study show that lower amount of fluctuating genes are generated in the presence of 2 b or 4 b, relative to that from exogenous delivery of let7a‐1. Because peptides 2 b and 4 b promote enhanced formation of mature let7a‐1 only at the endogenous miRNA level, this specifically controls genes related to let7a‐1.